Integrating simultaneous bi-direction signalling in the test fabric of 3D stacked integrated circuits. - Soomro, Iftikhar Ahmed (Cranfield University, 2021)
The world has seen significant advancements in electronic devices’ capabilities, most notably the ability to embed ultra-large-scale functionalities in lightweight, area and power-efficient devices. There has been an enormous push towards quality and reliability in consumer electronics that have become an indispensable part of human life. Consequently, the tests conducted on these devices at the final stages before these are shipped out to the customers have a very high significance in the research community. However, researchers have always struggled to find a balance between the test time (hence the test cost) and the test overheads; unfortunately, these two are inversely proportional. On the other hand, the ever-increasing demand for more powerful and compact devices is now facing a new challenge. Historically, with the advancements in manufacturing technology, electronic devices witnessed miniaturizing at an exponential pace, as predicted by Moore’s law. However, further geometric or effective 2D scaling seems complicated due to performance and power concerns with smaller technology nodes. One promising way forward is by forming 3D Stacked Integrated Circuits (SICs), in which the individual dies are stacked vertically and interconnected using Through Silicon Vias (TSVs) before being packaged as a single chip. This allows more functionality to be embedded with a reduced footprint and addresses another critical problem being observed in 2D designs: increasingly long interconnects and latency issues. However, as more and more functionality is embedded into a small area, it becomes increasingly challenging to access the internal states (to observe or control) after the device is fabricated, which is essential for testing. This access is restricted by the limited number of Chip Terminals (IC pins and the vertical Through Silicon Vias) that a chip could be fitted with, the power consumption concerns, and the chip area overheads that could be allocated for testing. This research investigates Simultaneous Bi-Directional Signaling (SBS) for use in Test Access Mechanism (TAM) designs in 3D SICs. SBS enables chip terminals to simultaneously send and receive test vectors on a single Chip Terminal (CT), effectively doubling the per-pin efficiency, which could be translated into additional test channels for test time reduction or Chip Terminal reduction for resource efficiency. The research shows that SBS-based test access methods have significant potential in reducing test times and/or test resources compared to traditional approaches, thereby opening up new avenues towards cost-effectiveness and reliability of future electronics.
Jennions, Ian K. - Associate Supervisor
Keywords: 3D stacked integrated circuits; system on chip; design for testability; simultaneous bi-directional signalling; test access mechanism; reduced pin-count testing; optimization